2017
DOI: 10.1007/s10068-017-0201-4
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of a novel Terminalia pectin

Abstract: This study reports the investigation into pectin present in -a native Australian fruit utilised in dietary supplement industry. Citric acid extraction was carried out to extract pectin from two commercially available products-frozen puree and freeze-dried puree powder. The yields of the extracted pectin were measured at various pHs (2.0, 3.0 and 4.0) and times (30, 60 and 120 min) at 75 °C. Pectin yield ranged between 4.8 and 21%. Freeze-dried powder had a higher pectin yield compared to puree. Extraction at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Moreover, MB mix gave its maximum yield at low pH contrarily to MP and PB mixes whose yields were maximum at high pH. This observation is similar to the results published by Chaliha et al (2017) [59]. They explained that Terminalia ferdinandiana has a high level of calcium (273-287 mg/100 g DW).…”
Section: Yields Of the Mixessupporting
confidence: 88%
“…Moreover, MB mix gave its maximum yield at low pH contrarily to MP and PB mixes whose yields were maximum at high pH. This observation is similar to the results published by Chaliha et al (2017) [59]. They explained that Terminalia ferdinandiana has a high level of calcium (273-287 mg/100 g DW).…”
Section: Yields Of the Mixessupporting
confidence: 88%
“…The results indicated that the addition of 0.1% icariin had little effect on the concentration of [15]. The region between 1800 and 1500 cm 21 of the spectra corresponds to infrared absorption by the carboxylic ester, and the region between 800 and 1200 cm 21 of the spectra corresponds to carbohydrate [18]. Vibrations of O-H are typically found around the 3432 cm 21 region [19].…”
Section: Discussionmentioning
confidence: 95%
“…The characteristic absorption bands of EP were at 3380, 2918, 2850, 1734, 1654, 1604, 1385, 1257, 1054 and 1033 cm −1 [15]. The region between 1800 and 1500 cm −1 of the spectra corresponds to infrared absorption by the carboxylic ester, and the region between 800 and 1200 cm −1 of the spectra corresponds to carbohydrate [18]. Vibrations of O-H are typically found around the 3432 cm −1 region [19].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, commercial pectin from the orange peel with an equivalent weight of 445.59 g / Ek was used [27]. While in some other studies used commercial pectin from orange peel and applesauce pulp which both have an equivalent weight of 893 g/Eq [28], [29]. Commercial pectin is generally extracted using a hydrochloric acid solution, so that most of the pectin obtained has a low molecular weight, due to its higher ionization strength when compared with the citric acid used in this study [7], [30].…”
Section: Discussionmentioning
confidence: 99%